The GRK2/AP‐1 Signaling Axis Mediates Vascular Endothelial Dysfunction and Atherosclerosis Induced by Oscillatory Low Shear Stress - Wu, Li‐Da; Shi, Yi; Kong, Chao‐Hua; Chen, Ai‐Qun; Kang, Ying; Kan, Jun‐Yan; Jiang, Xiao‐Min; Chu, Peng; Wang, Dong‐Chen; Lv, Yi‐Fei; Qian, Zhi‐Yuan; Jiang, Zi‐Hao; et al. (Advanced science, 2025)
Disturbed blood flow and the resulting oscillatory low shear stress (OSS) are key contributors to vascular endothelial dysfunction and the initiation of atherosclerosis. However, the molecular mediators that translate abnormal hemodynamic signals into pathological vascular endothelial responses remain unclear. G protein‐coupled receptors (GPCRs) are classical mechanosensors in the vascular endothelium. Here, using vascular endothelial‐specific knockout mice, in vitro parallel plate flow chamber systems, and phosphoproteomic analysis, G protein‐coupled receptor kinase 2 (GRK2) is identified as a central mediator of OSS‐induced vascular endothelial dysfunction. Mechanistically, OSS promotes GRK2 phosphorylation at serine 29, which subsequently activates the transcription factor activator protein‐1 (AP‐1), increasing the expression of the proinflammatory adhesion molecules intercellular cell adhesion molecule‐1 (ICAM1) and vascular cell adhesion molecule 1 (VCAM1). In parallel, AP‐1 promotes nuclear receptor subfamily 4 group A 1 (NR4A1) transcription, which anchors liver kinase B1 (LKB1) to the nucleus and suppresses downstream AMP‐activated protein kinase (AMPK) signaling, leading to metabolic dysregulation and impaired vascular endothelial homeostasis. These findings underscore the GRK2/AP‐1 signaling axis as a crucial mechanotransduction cascade linking disturbed flow to vascular endothelial dysfunction. Given the important role of GPCRs in mechanotransduction, targeting GRK2 may offer a novel therapeutic approach for atherosclerosis.